2021
DOI: 10.2147/rmhp.s321200
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Community Audio Towers in Health Education for Prevention of Cervical Cancer by Health Workers in Kyotera District, Uganda: A Cross-Sectional Study

Abstract: Purpose: Community audio towers (CATs) are a communication resource that can be utilized by public health practitioners to enhance health communication in rural and periurban settings. However, information on availability of this channel of communication for use in health education and promotion remains scanty. We determined the availability of CATs for use in cervical cancer health education among health workers for prevention of cervical cancer in Kyotera District, Uganda. Methods: Using a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…As such, integrating cervical cancer screening into health workers education packages and disseminating information via CATs may be effective health communication delivery mechanisms, where available. This may be feasible in Kyotera since a previous study found that the majority of the health workers believed CATs were accessible and easier to communicate on health issues; however, fewer than 20% used them [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, integrating cervical cancer screening into health workers education packages and disseminating information via CATs may be effective health communication delivery mechanisms, where available. This may be feasible in Kyotera since a previous study found that the majority of the health workers believed CATs were accessible and easier to communicate on health issues; however, fewer than 20% used them [ 43 ].…”
Section: Discussionmentioning
confidence: 99%